STYLISTIC FEATURES OF DIALECT WORDS IN THE LANGUAGE OF ARTISTIC WORKS - Suleymanova Ramila Yusif gizi (Theoretical Hypotheses and Empirical Results, 2024)
A process of constant change and enrichment is occur in the vocabulary of a language. Not all elements of a language that form its vocabulary are used in the same degree. İt is natural, because each lexical unit of a language has its own unique features and stylistic duties. Therefore, a group of words is used in all styles, while the other group is used only in a certain style carrying special stylistic purposes. In this sense, according usage in linguistic literature, words in vocabulary of a language are divided into different groups. Among them dialect and accent words take a special place . Dialect words are lexical units that have limited scope of usage. Dialect and accent words can mostly be found in art style. Dialects come into written literary language through fiction. Dialects and accents are sources of enrichment of vocabulary in Azerbaijani literary language. Besides written sources in studying of history of the Azerbaijani language live language plays a great importance as well particularly dialect and accent words.